2015
DOI: 10.1074/jbc.m115.638577
|View full text |Cite
|
Sign up to set email alerts
|

Mdm2 Promotes Myogenesis through the Ubiquitination and Degradation of CCAAT/Enhancer-binding Protein β

Abstract: Background: CCAAT/Enhancer-binding Protein ␤ (C/EBP␤) inhibits differentiation of muscle satellite cells and is rapidly down-regulated in early myogenesis. Results: The E3 ubiquitin ligase Mouse double minute 2 homolog (Mdm2) targets C/EBP␤ for degradation thereby promoting entry into myogenesis. Conclusion: Mdm2 expression is necessary for entry into myogenesis. Significance: Establishes a new role for Mdm2 in cellular differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 41 publications
8
48
0
Order By: Relevance
“…The transcription factor CCAAT/enhancer-binding protein b (C/EBPb), is an important regulator of mesenchymal stem cell fate and is upregulated in muscle wasting, such as sarcopenia [15]. Our work has shown that in healthy muscle, C/EBPb expression is localized to Pax7 + satellite cells and its expression is downregulated during myogenesis in parallel with Pax7 [16,17]. Forced expression of C/EBPb in myoblasts stimulates Pax7 expression, reduces MyoD protein expression, and inhibits myogenesis.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The transcription factor CCAAT/enhancer-binding protein b (C/EBPb), is an important regulator of mesenchymal stem cell fate and is upregulated in muscle wasting, such as sarcopenia [15]. Our work has shown that in healthy muscle, C/EBPb expression is localized to Pax7 + satellite cells and its expression is downregulated during myogenesis in parallel with Pax7 [16,17]. Forced expression of C/EBPb in myoblasts stimulates Pax7 expression, reduces MyoD protein expression, and inhibits myogenesis.…”
Section: Introductionmentioning
confidence: 90%
“…Our work has shown that in healthy muscle, C/EBPb expression is localized to Pax7 + satellite cells and its expression is downregulated during myogenesis in parallel with Pax7 [16,17]. Forced expression of C/EBPb in myoblasts stimulates Pax7 expression, reduces MyoD protein expression, and inhibits myogenesis.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In healthy muscle, satellite cells express C/EBPb which inhibits myogenic differentiation 9,10 . Upon induction of differentiation, C/EBPβ expression dramatically decreases, allowing differentiation to proceed [9][10][11] . We observed that the anti-C/EBPb antibody (E299, ab32358) also detects myosin light chain 4 (MYL4) in differentiating myoblasts and in other cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…In skeletal muscle, C/EBPβ expression is localized to Pax7 + SCs of healthy muscle and is rapidly downregulated upon induction to differentiate [19, 20]. In vivo, loss of C/EBPβ expression in SCs resulted in larger muscle fiber cross-sectional area, fewer fibers, and improved repair after a single acute muscle injury [19, 20]. When overexpressed in the murine myoblast cell line C2C12 or in primary myoblasts, C/EBPβ reduced MyoD and other myogenic protein levels during differentiation, in addition to reducing myoblast fusion.…”
Section: Introductionmentioning
confidence: 99%